Understanding the pH Dependence of Supersaturation State-A Case Study of Telmisartan - Szabina Kádár; Dóra Csicsák; Petra Tőzsér; Attila Farkas; Tamás Pálla; Arash Mirzahosseini; Blanka Tóth; Gergő Tóth; Béla Fiser; Péter Horváth; János Madarász; Alex Avdeef; et al. (MDPI AG, 2022)
Creating supersaturating drug delivery systems to overcome the poor aqueous solubility of active ingredients became a frequent choice for formulation scientists. Supersaturation as a solution phenomenon is, however, still challenging to understand, and therefore many recent publications focus on this topic. This work aimed to investigate and better understand the pH dependence of supersaturation of telmisartan (TEL) at a molecular level and find a connection between the physicochemical properties of the active pharmaceutical ingredient (API) and the ability to form supersaturated solutions of the API. Therefore, the main focus of the work was the pH-dependent thermodynamic and kinetic solubility of the model API, TEL. Based on kinetic solubility results, TEL was observed to form a supersaturated solution only in the pH range 3-8. The experimental thermodynamic solubility-pH profile shows a slight deviation from the theoretical Henderson-Hasselbalch curve, which indicates the presence of zwitterionic aggregates in the solution. Based on pKa values and the refined solubility constants and distribution of macrospecies, the pH range where high supersaturation-capacity is observed is the same where the zwitterionic form of TEL is present. The existence of zwitterionic aggregation was confirmed experimentally in the pH range of 3 to 8 by mass spectrometry.